Pengaruh pelatihan dan motivasi kerja terhadap kinerja karyawan PT. PLN (Persero) Cabang Pekanbaru - Fathindra, Muhammad Yusuf; ', Marzolina; ', Taufiqurrahman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this research to explain the effects of Training and Work Motivation simultaneously and partially on Employee Performance at The Branch of Pekanbaru This research used pimary data that obtained from interviews and the questionnaire to all employees at The Branch of Pekanbaru Secondary data relating to organizational structure. Population in this research were all employees that consist of 81 people. Methods of analysis used in this research is the method of multiple linear regression.The results of the testing that has been done, simultaneous regression test (uji-F) suggests that Training and Work Motivation variables simultaneously have significant effect on Employee Performance. On the partial test (uji-t) results indicate that the variables of Training and Work Motivation are partially significant efeect on Employee Performance. This writer concluded that the variable of Training and Work Motivation simultaneously and partially influenced positively and significantly toward Employee Performance PT. PLN (Persero) the Branch Of Pekanbaru.Keywords : Training, Work Motivation and Employee Performance